2016
DOI: 10.1080/00071668.2016.1180667
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Lactobacillus isolates from gastrointestinal tract of guinea fowl for probiotic qualities using in vitro tests to select species-specific probiotic candidates

Abstract: A total of 32 Lactobacillus isolates, 8 each from the crop (LGFCP1-LGFCP8), proventriculus (LGFP9-LGFP16), ileum (LGFI17-LGFI24) and caeca (LGFCM25-LGFCM32) were isolated from 25 adult guinea fowl (Pearl variety), 22-28 weeks of age, and characterised morphologically, physiologically, biochemically and by molecular methods. Isolates were screened for their probiotic quality using range of in vitro tests: aggregation test, cell surface hydrophobicity, resistance to bile salts and acidic conditions, enzymatic te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…In the present study, all these 28 isolates with short aggregation time and high hydrophobicity were selected for further screening as these properties indicated the adhesion ability to gastrointestinal tract (GIT) epithelium. Our results were in agreement with Vineetha et al (2016) from India who reported higher cell surface hydrophobicity (above 76%) for Lactobacillus isolates. Ehrmann et al (2002) reported that values higher than 66% were regarded as strong hydrophobicity.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…In the present study, all these 28 isolates with short aggregation time and high hydrophobicity were selected for further screening as these properties indicated the adhesion ability to gastrointestinal tract (GIT) epithelium. Our results were in agreement with Vineetha et al (2016) from India who reported higher cell surface hydrophobicity (above 76%) for Lactobacillus isolates. Ehrmann et al (2002) reported that values higher than 66% were regarded as strong hydrophobicity.…”
Section: Resultssupporting
confidence: 83%
“…Ehrmann et al (2002) reported that values higher than 66% were regarded as strong hydrophobicity. Resistance to low pH and bile salts is a characteristic feature of probiotic strains for survival in the GIT (Vineetha et al, 2016). A total of 20 (L2, L6, L8, L11, L12, L13, L14, L15, L16, L17, L18, L20, L26, L31, L33, L35, L36, L38, L41 and L42) out of 28 isolates showed satisfactory growth at pH 2 and 3, while other isolates showed very meager growth.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations